Strong feelings : emotion, addiction, and human behavior - Elster, Jon, 1940- (Jean Nicod lectures ;, 1999)
"The book is organized around parallel analyses of emotion and addiction in order to bring out similarities as well as differences. Elster's study sheds fresh light on the generation of human behavior, ultimately revealing how cognition, choice, and rationality are undermined by the physical processes that underlie strong emotions and cravings. This book will be of particular interest to those studying the variety of human motivations who are dissatisfied with the prevailing reductionisms."--Jacket